The History of Violence on Pain vs. Pleasure: A Functionalistic and Dramatisation Concept of Social Phenomenon - Gulpham, Shahanshah; Shekhar, Pravesh (International Journal of Criminology and Sociology, 2026)
Theorising the law of confidence in a heuristic method clearly indicates that the violence is based on immediate pleasure for misdemeanour and results in severe pain for the victim. Historically speaking, pain and pleasure are the two sides of a single coin. Design of criminality, as proved in the writing of Jeremy Bentham, a philosopher of legal history, that morality plays a tremendous role, in which detachment of morality from the individual encourages harm to others, and vice versa, attachment of morality moulds the individual to encourage pleasure. The functionalistic approach of crime is argued for societal necessity. According to E. Durkheim, crime or violence is the social fact by which a society is functional and also proves its existence. Other socio-legal processing institutions, such as the court, police, prison, and prosecution, have historically interlinked and co-exist as a functional unit of the whole society. Enemies of social coherence represent themselves in a dramatised way and try to improve their existence by inflicting pain on others through their violent modus operandi. The present research paper provides multiple theoretical explanations with regard to the historical writing about violence. The paper also talks about the guilty mind of offenders and justice delivery services in the past. The future perspective of violence and how to practice the penalty for changing the pace of violence.